The Political Thought of John Holloway Struggle, Critique, Emancipation - García Vela, Alfonso; Bonnet, Alberto (Cham Palgrave Macmillan, 2023)
This book provides renewed reflection and critical discussion on John Holloway's political and theoretical thought. Two decades ago, in Change the World without Taking Power, Holloway set out on a path that he followed a decade later in Crack Capitalism and continues to walk today with his new book, Hope in Hopeless Times. The contributions in this volume critically analyze his innovative attempt to rethink the meaning and dynamics of revolution in the conditions of contemporary capitalism. More than ten years after the publication of Crack Capitalism, this volume aims to question Holloway's attempt, as well as his theoretical foundations in his original rereading of Marxism and Critical Theory and their relations with the characteristics adopted by the anti-capitalist struggles during the last two decades. Its authors, from different geographies, traditions, and scientific disciplines, establish throughout its pages a fruitful dialogue convened by Holloway's innovative ideas. Alfonso García Vela is Professor and Researcher at the Instituto de Ciencias Sociales y Humanidades at the Benemérita Universidad Autonóma de Puebla, México. Alberto Bonnet is Professor and Researcher at the Department of Economics and Administration of the National University of Quilmes, Argentina
Chapter 1. John Holloway and the Meaning of Revolution Today (Alfonso García Vela & Alberto Bonnet) -- Part I: Marxism and Political Theory -- Chapter 2. On Domination and its Fragility (Richard Gunn & Adrian Wilding) -- Chapter 3. Suffering and its Social Validation: On Abstract Labour (Werner Bonefeld) -- Chapter 4. Class, Contradiction and Antagonism (Adrián Piva) -- Chapter 5. An 18th Century Ancestor of Crack Capitalism: How Rousseau’s Radical Democracy helps us Open Cracks in Capitalism (Yiorgos Moraitis & Vasilis Grollios) -- Part II: Struggles, Critique, and Emancipation -- Chapter 6. Ontologizing negativity: the political consequences of the tension between doing and the cracks (Edith González & Panagiotis Doulos) -- Chapter 7. Cracking the Everyday Life: Discipline and Emancipation in the Pandemic Era (Katerina Nasioka & Marios Panierakis) -- Part III: Holloway and Critical Theory -- Chapter 8. Holloway and Marcuse: The Foundation ofNegative Subjectivity (Alfonso García Vela) -- Chapter 9. The crisis of capital and the conformist rebellion: on the need to reflect on the false solutions (José A. Zamora) -- Chapter 10. John Holloway and the Dialectic of Revolution (Alberto Bonnet) -- Chapter 11. Doing the Locomotive: on Running towards Disaster, Being the Disaster and some bad Screams in John Holloway's Contributions to Open Marxism 4 (Marcel Stoetzler).-Afterword (John Holloway).
Keywords: Political Theory; Marxian economics; Critical theory; Critical Theory; Labor Economics; Marxist Economics; Marxian school of sociology; Political science; Marxist Sociology; Labor economics